PENGARUH KEMASAKAN BUAH TERHADAP MUTU BENIH JARAK PAGAR (Jatropha curcas L.) - Adikadarsih, Sri; Anam, Choirul (Universitas Islam Darul Ulum, 2009)
This paper examined pair wise comparison matrix (PC) used to construct the decision model known as the Analytic Hierarchy Process (AHP). AHP is a decision method based on diversity criteria. One of the methods used to obtain the AHP priority vectors are Eigen value method. Consistency matrix that is used is very important in supporting a valid decision. In this project, it will discuss the influence of disturbance on the consistency ratio of the matrix PC. Vector behavior will be also discussed priorities when pair wise comparison matrix interference and also subject to special review of the disorders that cause the reversal of dominance against the decision.